SOCS1 Mimetics and Antagonists: A Complementary Approach to Positive and Negative Regulation of Immune Function - Ahmed, Chulbul M. I.; Larkin, Joseph; Johnson, Howard M. (Frontiers in Immunology, 2015)
Suppressors of cytokine signaling (SOCS) are inducible intracellular proteins that play essential regulatory roles in both immune and non-immune function. Of the eight known members, SOCS1 and SOCS3 in conjunction with regulatory T cells play key roles in regulation of the immune system. Molecular tools such as gene transfections and siRNA have played a major role in our functional understanding of the SOCS proteins where a key functional domain of 12 amino acid residues called the kinase inhibitory region (KIR) has been identified on SOCS1 and SOCS3. KIR plays a key role in inhibition of the JAK2 tyrosine kinase which in turn plays a key role in cytokine signaling. A peptide corresponding to KIR (SOCS1-KIR) bound to the activation loop of JAK2 and inhibited tyrosine phosphorylation of STAT1α transcription factor by JAK2. Cell internalized SOCS1-KIR is a potent therapeutic in the experimental allergic encephalomyelitis (EAE) mouse model of multiple sclerosis and showed promise in a psoriasis model and a model of diabetes associated cardiovascular disease. By contrast, a peptide, pJAK2(1001-1013), that corresponds to the activation loop of JAK2 is a SOCS1 antagonist. The antagonist enhanced innate and adaptive immune response against a broad range of viruses including herpes simplex virus, vaccinia virus, and an EMC picornavirus. SOCS mimetics and antagonists are thus potential therapeutics for negative and positive regulation of the immune system.